Evaluation of the Effectiveness of Tax Dispute Resolution in Realizing Justice in the Tax Court - R. Narendra Jatna; Hasbullah Hasbullah; Abdul Kadir Jaelani (Jurnal Al-Hakim: Jurnal Ilmiah Mahasiswa, Studi Syariah, Hukum dan Filantropi, 2026)
The increase in the intensity of audits and digitalization of tax administration in Indonesia has encouraged an increase in the number of tax disputes, thus demanding a resolution mechanism that is not only administratively efficient, but also able to ensure objectivity, substantive justice, and legal certainty. This study aims to analyse the effectiveness of the tax dispute resolution mechanism, especially at the objection stage at the Directorate General of Taxes (DGT) and the appeal stage at the Tax Court, and examine the implications of institutional reform after the Constitutional Court Decision Number 26/PUU-XXI/2023 and the development of tax digitalisation on the quality of dispute resolution. The discussion was carried out by examining the structure of the objection authority, the quasi-judicial character of the Tax Court, and the use of electronic evidence in the trial process. The results of the study show that the objection mechanism has not functioned optimally as an initial filter for disputes because of structural conflicts of interest, information asymmetry, low transparency, and a lengthy process; therefore, it is often perceived as an administrative formality. At the appellate level, the Tax Court faces a backlog of cases, the complexity of modern tax disputes, and the limited capacity and consistency of judges' considerations, which affect the predictability of decisions. Thus, it is concluded that institutional reform and tax digitalisation have the potential to strengthen the independence and efficiency of tax dispute resolution; however, regulatory harmonisation, institutional capacity building, and strengthening electronic evidentiary standards are required to realise a fair and credible tax dispute resolution system.